Comparison of Indonesian and Malaysian Media in Reporting the QZ8501 Plane Crash Crisis - Mohd Ajis, Siti Zaiton; Mohamad, Emma Mirza Wati (International Journal of Media and Communication Research, 2025)
The tragic loss of Flight QZ8501 captured widespread attention in 2014. The incident resulted in numerous fatalities with various forms of reporting and affecting AirAsia's negative image, such as pilot and staff incompetence, aircraft system weaknesses, management shortcomings, and safety issues are often associated when such unfortunate events befall an airline. This study attempts to examine the types of news reporting by local Indonesian media (Kompas.com and Detik.com) and Malaysian media (Berita Harian and Astro Awani) related to the QZ8501 incident, which ultimately shapes the image of AirAsia. The study found similarities between both Indonesian and Malaysian local media in reporting news related to the QZ8501 crash, emphasizing important information, using a positive tone to respect the families of the victims, and avoiding sensationalism in accordance with journalistic ethics and the theory of social responsibility. This study highlights the promptness of AirAsia Malaysia and AirAsia Indonesia's management in handling the crisis by providing information and interacting with the media and victims' families from day one, as reflected in the media coverage. Indirectly, such reporting can positively influence the airline's image in crisis management as recognized through the Priority Integration Award at the 2015 ASEAN Business Awards. and may serve as a valuable guideline for future crisis handling.